An exploratory study of investment behaviour of investors. (7th June 2017) - Mak, Mark KY; Ip, WH
The financial industry plays a significant role in Mainland Chinese and Hong Kong economies and has aroused increasing managerial and academic interests in recent decades. Individual investors are becoming more cautious towards financial investment which makes it difficult for financial service providers to formulate marketing strategies after experiencing several financial crises. Prior research has suggested that financial investment behaviour would be affected by various factors, including the demographic characteristics of individuals; however, they seldom study the differences in financial investment behaviour between Mainland Chinese and Hong Kong investors or provide an easy-to-use approach for practical usage. This exploratory study aims at filling the identified research gap by proposing linear regression models of the financial investment behaviour of Mainland Chinese and Hong Kong investors. Based on the results of regression analyses, (i) there exist significant differences in financial investment behaviour between Mainland Chinese and Hong Kong investors, and (ii) investors' psychological, sociological and demographic factors are significant predictors of their investment behaviour/preferences. Thus, financial service providers are able to predict the investment behaviour/preference of its customers and formulate marketing and strategic decisions, such as customizing the financial investment portfolio of customers on the basis of regression models built.